Blastocyst euploidy rates in low-prognosis patients according to the POSEIDON criteria: a retrospective analysis of 3016 embryos. Issue 2 (February 2022) - Luo, Mingyue; Li, Duan; Xia, Mingdi; Xie, Hongqiang; Liu, Peihao; Qin, Yingying
Abstract: Research Question: Do embryo euploidy rates differ in the four groups of women with low prognosis as stratified by the POSEIDON criteria? Design: This was a retrospective cohort study of low-prognosis patients who met the POSEIDON criteria and underwent preimplantation genetic testing for aneuploidies (PGT-A) from January 2013 to June 2020 at the Center for Reproductive Medicine, Shandong University, China. A total of 3016 blastocysts from 1269 PGT-A cycles were included in the study. The primary outcome was the euploidy rate of the blastocysts. For each group, regression analyses were performed to quantitatively describe the relationship between maternal age and embryo euploidy rate. Results: The euploidy rate of embryos in women with poor ovarian response (POR) was 39.1% in total. There were 727, 1052, 275 and 962 blastocysts in groups 1, 2, 3 and 4, respectively, with corresponding embryo euploidy rates of 57.2%, 34.9%, 52.4% and 26.2% ( P < 0.001). Within each group, the euploidy rate decreased with age, especially in women aged 35 years or older (i.e. groups 2 and 4). Conclusions: Euploidy rates were more favourable in groups 1 and 3, of a young age, re-emphasizing that oocyte quality is the primary factor determining embryo euploidy rate. The study's findings demonstrated the reasonability of categorizing women with POR by the POSEIDON criteria depending on female age and ovarian reserve biomarkers. These results also provide information for women with POR in different subgroups so they can receive proper counselling on the possible prognosis.